3D Microphysiological System‐Inspired Scalable Vascularized Tissue Constructs for Regenerative Medicine (Adv. Funct. Mater. 1/2022). (3rd January 2022) - Bang, Seokyoung; Tahk, Dongha; Choi, Young Hwan; Lee, Somin; Lim, Jungeun; Lee, Seung‐Ryeol; Kim, Byung‐Soo; Kim, Hong Nam; Hwang, Nathaniel S.; Jeon, Noo Li
Abstract : Vascularized Tissue Constructs In article number 2105475, Hong Nam Kim, Nathaniel S. Hwang, Noo Li Jeon, and co‐workers report a scalable method for engineering vascularized tissue constructs inspired by the vasculogenesis‐induction method and its application in ischemic tissue regeneration.